Differential expression profiles of circular RNAs in the rat hippocampus after deep hypothermic circulatory arrest. Issue 8 (8th March 2021) - Li, Yi‐Ai; Liu, Zhi‐Gang; Zhang, You‐Peng; Hou, Hai‐Tao; He, Guo‐Wei; Xue, Lan‐Gang; Yang, Qin; Liu, Xiao‐Cheng
Abstract: Neurological dysfunction commonly occurs after cardiac surgery with deep hypothermic circulatory arrest (DHCA). The mechanisms underlying DHCA‐associated brain injury remain poorly understood. This study determined the changes in expression profiles of circular RNAs (circRNAs) in the hippocampus in rats that underwent DHCA, with an attempt to explore the potential role of circRNAs in the brain injury associated with DHCA. Adult male Sprague Dawley rats were subjected to cardiopulmonary bypass with DHCA. Brain injury was evaluated by neurological severity scores and histological as well as transmission electron microscope examinations. The expression profiles of circRNAs in the hippocampal tissues were screened by microarray. Quantitative real‐time PCR (RT‐qPCR) was used to validate the reliability of the microarray results. Bioinformatic algorithms were applied to construct a competing endogenous RNA (ceRNA) network, and Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses were performed to explore the potential biological roles of the circRNAs. Out of 14 145 circRNAs screened, 56 were differentially expressed in the hippocampus between the DHCA and sham‐operated rats, including 30 upregulated and 26 downregulated circRNAs. The expression changes of six selected circRNAs (upregulated: rno_circRNA_011190, rno_circRNA_012988, rno_circRNA_000544; downregulated: rno_circRNA_010393, rno_circRNA_012043, rno_circRNA_015149) were further confirmed by RT‐qPCR. Bioinformatics analysis showed the enrichment of these confirmed circRNAs and their potential target mRNAs in several KEGG pathways including histidine metabolism, adipocytokine signaling, and cAMP signaling. By revealing the change expression profiles of circRNAs in the brain after DHCA, this study indicates possible involvements of these dysregulated circRNAs in brain injury and suggests a potential of targeting circRNAs for prevention and treatment of neurological dysfunction associated with DHCA. Abstract : Rats that underwent deep hypothermic circulatory arrest (DHCA) showed compromised neurological function and damage of hippocampal neurons. Microarray revealed 56 differentially expressed circRNAs in the hippocampal tissues in rats that underwent DHCA including 30 upregulated and 26 downregulated ones. Further bioinformatics analysis of six selected circRNAs that were validated by RT‐qPCR provided new insights into the role of circRNAs in the development of brain injury after DHCA.